Synthesis, characterization, biological screening and molecular docking of Zn(II) and Cu(II) complexes of 3, 5‐dichlorosalicylaldehyde‐N4‐cyclohexylthiosemicarbazone. (23rd November 2019) - Mathews, Nimya Ann; Begum, P.M. Sabura; Kurup, M.R. Prathapachandra
Abstract : A 3, 5‐dichlorosalicylaldehyde‐N 4 ‐cyclohexylthiosemicarbazone (C14 H16 Cl2 N3 OS) and its complexes [Zn(dsct)(phen)]·DMF (1 ), [Zn(dsct)(bipy)]·DMF (2 ), [Cu(dsct)(bipy)]·DMF (3 ) (phen = 1, 10‐phenathroline, bipy = 2, 2'bipyridine) were synthesized and characterized by CHN analysis, FT‐IR, UV–vis and NMR spectra. The molecular structure of the thiosemicarbazone (H2 dsct) and its complexes have been resolved using single crystal XRD studies. In the complexes, thiosemicarbazone exist in the thioiminolate form and acts as dideprotonated tridentate ligand coordinating through phenolic oxygen, thioiminolate sulfur and azomethine nitrogen. The antibacterial activity of the prepared compounds were screened against Escherichia coli, Salmonella typhi, Enterobacter aerogenes, Shigella dysentriae, Bacillus cereus, Staphylococcus aureus . All the complexes showed activity against bacterial strains E.coli and Salmonella typhi . The thiosemicarbazone showed activity against three bacterial strains such as E. coli, Enterobacter aerogenes and Shigella dysentriae . Complex 2 showed very good antibacterial activity as compared to standard drug (Ampicillin) against the bacterial strain, Salmonella typhi . Finally, the thiosemicarbazone and its complexes have been used to accomplish molecular docking studies against an Epidermal Growth Factor Receptor (EGFR) and breast cancer mutant 3hb5‐oxidoreductase to determine the most preferred mode of interaction. The results confirm that the complex [Cu (dsct)(bipy)]·DMF(3 ) showed the highest docking score as compared to other complexes under study. The [Cu(dsct)(bipy)]·DMF(3 ) complex was evaluated for their anticancer activities against breast cancer cell line (MCF‐7) and normal L929 (Mouse Fibroblast) cell line. It was found that the compound showed an LC50 of 6.25 μg/mL against breast cancer cell line (MCF‐7). Abstract : 3, 5‐Dichlorosalicylaldehyde‐N 4 ‐cyclohexylthiosemicarbazone and its mononuclear Zn(II) and Cu(II) complexes have been synthesized and characterized. Molecular structures of metal complexes were determined using single crystal X‐ray diffraction studies. Molecular docking studies against an Epidermal Growth Factor Receptor(EGFR) and breast cancer mutant 3hb5‐oxidoreductase were carried out. Anticancer activity against MCF‐7 breast cancer cell line is checked via MTT assay